A Multiple Primary Malignancy Patient With FANCA Gene Mutation: A Case Report and Literature Review - Xia, Qing; Zhao, Ling-Yi; Yan, Yi-Dan; Liao, Yuan; Di, Ying-San; Xiao, Xiu-Ying (Frontiers in Oncology, 2020)
Background: Multiple primary malignancies (MPMs) refer to two or more primary malignant tumors in the same individual, the prevalence of which ranges from 0. 734 to 11.7%. The risk factors for MPMs vary and include both genetic and environmental causes. FANCA gene mutation might be a predisposition to the development of a second primary cancer. Here, we report a case in which a patient with a FANCA mutation developed thyroid papillary carcinoma and gastric adenocarcinoma. Case Presentation: A 48-year-old woman was diagnosed with thyroid cancer underwent resection in 2006. In 2008, the patient developed gastric adenocarcinoma and underwent radical gastrectomy. Gastric cancer was completely remitted after radiochemotherapy, but metastasis developed, and she received immunotherapy. The patient died on October 27, 2019. Peripheral blood gene detection showed germline FANCA mutation. Conclusions: Gene detection is of great importance in cancer patients, especially in those with MPMs. FANCA mutation is a predisposition to tumorigenesis that can increase the risk of developing MPMs. Patients with heterozygous FANCA gene mutations have poorer outcomes.